PERAN HUMAS DALAM MEMBENTUK CITRA KOTA BENGKULU (Studi pada Humas Pemerintah Kota Bengkulu) - Indria - (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
Public Relations Department of Bengkulu City assigned to form the image of Bengkulu City Government through a variety of media used. In practice, the PR Department of Bengkulu city has not carry out all the roles and tasks entrusted optimally because of the tendency to deliver the information is still one-way. Several of the barrier factors are: political factor, the existing organizational structure in the Bengkulu City, inadequate infrastructure to support public relations activities, and lack of coordination between the public relation departments that exist in the Provincial and City Government of Bengkulu. While some of the supporting factors of the role and duties implementation are: the funding is sourced directly from Bengkulu City budget in the implementation of public relations activities of the city of Bengkulu, and the motivation to improve the quality and quantity of human resources.Keywords: Public Relation, Image